CCNP wireless IUWMS quick reference - Henry, Jerome (Cisco Press, 2010)
"The 642-746 IUWMS Implementing Cisco Unified Wireless Mobility Services exam is one of four exams associated with the CCNP Wireless certification. This exam assesses a candidate's capability to integrate mobility services into the WLAN, to tune and troubleshoot the WLAN, and to implement indoor enterprise mesh networks. Candidates can prepare for this exam by taking the IUWMS Implementing Cisco Unified Wireless Mobility Services course. As a final exam preparation tool, the CCNP Wireless (IUWMS) Quick Reference provides a concise review of all objectives on the new Implementing Cisco Unified Wireless Networking Essentials (IUWNE) Exam (640-721). This digital ebook provides you with detailed, graphical-based information, highlighting only the key topics in a cram-style format"--Resource description page.